A Missing Link between Musicology and Music? New Insights from the Philosophy of Complexity and the Musical Heuristics - Mandolini Ricardo (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
This chapter postulates the need to include Edgar Morin’s philosophical principles of complexity as complements to the musicological panoply of analyses and interpretations coming from musical semiology and musicology. In this way, a new critical approach can be given to such analyses, adopting a polysemic attitude that suits better than the current one to convey the full richness of the musical phenomenon, especially in terms of its fluidity and dynamics. The first part of the article attempts to determine the limits of Jean-Jacques Nattiez’s musical semiology, as well as the analyses derived from it. We will look closely at the notion of musical work examining the components of its complexity, which prevents a reductive operation between the score and the work. The second part of the chapter deals with the reconstruction of musical works, proposed on the basis of Musical Heuristics, giving way to an "embodied" knowledge of the reference pieces and thus complementing the analyses derived from musical semiology. As conclusion, my paper attempts a musicological application of the three underlying principles of the philosophy of complexity.